Application of Dorothea Orem's Self-Care Theory in Patients with Diabetic Ulcers: A Mixed-Methods Case Study - Suciana, Fitri; Rayasari, Fitrian (Chakra Brahmanda Lentera Institute, 2026)
Background: Diabetes Mellitus is a metabolic disease with an increase in blood sugar levels above normal, which can cause complications if not properly managed. One of the complications that can arise is diabetic ulcers, which require nursing interventions after debridement or post-amputation. Methods: This study employed a mixed-methods approach, combining both quantitative data and a case study design. Following STROBE guidelines, the quantitative component included 19 individuals diagnosed with diabetes mellitus. Using purposive sampling, 7 participants were selected based on the inclusion criteria of having diabetic ulcers and being hospitalised for at least 3 days, and 5 nurses who cared for the patients. Data were collected using structured observation sheets and nursing care records. For the qualitative component, guided by COREQ criteria, in-depth interviews were conducted using semi-structured interview guides to explore patients' experiences and perceptions. Data analysis for the qualitative data used grounded theory methodology, while descriptive statistics were applied to the quantitative data. NVivo software was used for qualitative coding, while SPSS was employed for descriptive analysis. Results: Orem's theory can be used in self-care efforts by carrying out wholly compensatory system nursing interventions, such as wound care, monitoring infections, and carrying out antibiotic treatment, while partially compensatory systems can be carried out by patients independently, such as insulin treatment at home, physical activity, and not smoking, while supportive educative systems by providing foot care education by assessing foot health status. Orem's theory can be used in self-care efforts by performing wholly compensatory system nursing interventions with education, and patients can perform self-care with partially compensatory systems, such as physical activity, not smoking, and insulin use. Conclusion: Self-care nursing interventions for diabetic ulcers include partially compensatory and totally compensatory systems.